AUDITOR PERCEPTION OF CLOUD TECHNOLOGY-BASED AUDITS - Franco Benony Limba; Shella Gilby Sapulette; Theresia Febiengry Sitanala (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The rapid development of information technology has driven significant transformations in audit practices, one of which is through the adoption of cloud computing technology. This study discusses auditors' perceptions of cloud-based audits, including their views on the benefits, challenges, and professional implications of using the cloud in the audit process. The results of the study indicate that the majority of auditors view cloud technology as a tool that can improve audit efficiency, flexibility, and accuracy, especially through real-time data access and integration with analytical tools. However, on the other hand, concerns also arise regarding data security, technological competence, and dependence on cloud service providers. Differences in the level of readiness between large and small audit firms also affect the adoption pattern of this technology. This study emphasizes the importance of increasing technological literacy among auditors, developing cloud-based audit standards, and institutional support so that digital transformation in audits can take place optimally and sustainably.